Understanding the effect of formulation on functionality of modified chitosan films containing carvacrol nanoemulsions. (December 2016) - Tastan, Özge; Ferrari, Giovanna; Baysal, Taner; Donsì, Francesco
Abstract: The interest towards the use of films and coatings in food preservation has been reinforced in the recent years by the development of biopolymeric matrices incorporating essential oil as antimicrobial barriers in food as an alternative to synthetic additives. This work has therefore been addressed to investigate the effect of composition parameters on antimicrobial activity and properties of films based on modified chitosan containing different types of carvacrol nanoemulsions. Specifically, response surface methodology, applied for the concentration of biopolymer and carvacrol nanoemulsion in the film forming dispersions to maximize the antimicrobial activity against two model microorganisms, Escherichia coli and Listeria innocua, as well as surface hydrophobicity, was used to determine the optimum conditions for comparison of most promising systems. Results showed that emulsion formulations had a significant effect on the intrinsic antimicrobial activity, but also that their interaction with the modified chitosan matrix affected film properties and resulting bactericidal action. The two most active emulsion formulations, based on a combination of polysorbate 20 and glycerol monooleate, and on whey protein isolates, respectively, when incorporated in modified chitosan films significantly increased the inhibition zone against E . coli and L . innocua from 7.2–7.4 mm (modified chitosan alone) to 13.4–16.1 mm, while still ensuring surface hydrophobicity of the film. In comparison to the use of pure carvacrol, the encapsulation into nanoemulsions also fostered the production of more homogeneous films with better appearance. This work hence contributes to promoting, through the advancement of the knowledge in the field, the incorporation of nanoemulsions of essential oils in edible films and coatings for integrated food preservation strategies. Graphical abstract: Highlights: Different carvacrol nanoemulsions were developed with diverse antimicrobial activity. Most active carvacrol nanoemulsions were incorporated into modified chitosan films. Optimum film composition was determined using response surface methodology. Incorporation of nanoemulsions into modified chitosan ensured high film homogeneity. Carvacrol significantly increased modified chitosan intrinsic antimicrobial activity.